Airports for the future proceedings of the conference sponsored by the Institution of Civil Engineers ...[et al.] and held at the Institution of Civil Engineers, 11-12 April, 1967. (Institution of Civil Engineers, 1967)
With airport design and construction continuing to be a challenge to civil engineers, these proceedings contribute to the sharing of knowledge necessary for the development of technical improvements.